Satisfaction of Patients with Type II Diabetes on Health Service in Specialized Center for Endocrinology and Diabetes /Baghdad 2019 - Nazik L Kadium (مجله كليه طب الكندي, 2020)
Background: Patient satisfaction is of increasing importance and widely recognized as an important indicator of quality of the medical care. There was no homogeneous definition of patient satisfaction, since satisfaction concerns different aspects of care or settings, as well as care given by various professions.